The Status of Pediatric Patients With Hematologic Malignancy During COVID-19 Pandemic in Wuhan City, China. Issue 1 (January 2022) - Wang, Zhujun; Shen, Yaqing; Jin, Runming; Yu, Hui; Zhou, Fen; Xu, Jiawei; Qiu, Yining; Wang, Lin; Wu, Xiaoyan
Abstract : Data regarding the epidemiologic characteristics and clinical features of pediatric hematologic patients are limited in this corona virus disease 2019 (COVID-19) crisis. We investigated the status of 113 pediatric hematologic patients in Wuhan union hospital during the COVID-19 pandemic from January 23 to March 10, 2020. All the patients had routine blood and biochemical examination, as well as chest computed tomography scans, and the nucleic acid, immunoglobulin G-immunoglobulin M combined antibodies tests for SARS-CoV-2. After admission, all patients were single-room isolated for 5 to 7 days. The results showed that only 1 (0.88%) child with leukemia was confirmed to have SARS-CoV-2 infection and 15 (13.2%) children were considered as suspected cases. Comparing to the nonsuspected patients, the suspected cases had lower white blood cell count, hemoglobin level, neutrophil count, serum calcium ion level and serum albumin concentration, as well as higher levels of C-reactive protein. All the suspected cases were ruled out of SARS-CoV-2 infection by twice negative tests for the virus. Therefore, the incidence of SARS-CoV-2 infection in hematologic malignancy children was low during the COVID-19 pandemic in China. COVID-19 got early detected and the virus spread out in the ward was effectively blocked by increasing test frequency and using single-room isolation for 5 to 7 days after admission.